Diseño de un Plan de cobros por planillas para la junta de agua potable de la parroquia Canuto - Manabí. - Calderón Carranza, Carmen Clarivel (2011)
The present study was conducted to design a plan for the recovery of bills through a software in the Water Supply Board in the parish of Canuto, which served as a database and was intended to improve the administrative the institution. For the development of this work were implemented different types of research: applying field research, literature research who helped to obtain the results that would meet the objectives. In the implementation of each of these research processes were used different sources of information such as interviews, surveys and collection of bibliographic data, these tasks were conducted during six months, which were divided into three stages set out on schedule activities allowing the normal development control process. In the implementation of the survey it was taken a representative sample of 311 people of the affected population and interviews were applied to the officials of the Water Supply Board in Canuto, this information was tabulated and analyzed according to the purposes for which it was made, the results were accurate that would meet the objective, which was aimed to improve the living conditions of the inhabitants. Also the paper presents the development of a database that will facilitate the collection of the payroll.